Can robots tackle late-life loneliness? Scanning of future opportunities and challenges in assisted living facilities - Pirhonen, Jari (Futures, 2020)
This future-oriented study examines the opportunities and challenges offered by social robots and communication technology when aiming to decrease emotional and social loneliness in older people residing in assisted living (AL). The paper draws on prior literature on loneliness, elder care and social robots. The aim is to scan the futures regarding technology support for the frail older people in future AL. The analytical frame was built on Robert Weiss’ division of relational functions: attachment, social integration, opportunity for nurturance, reassurance of worth, sense of reliable alliance, and guidance in stressful situations, and on a distinction between direct and indirect social robots. Our examinations show that social robots could tackle both emotional and social loneliness in assisted living by empowering people to engage in different forms of social interaction inside and outside the facility. However, ethical concerns of objectification, lack of human contact, and deception need to be thoroughly considered when implementing social robots in care for frail older people.